The Influence Of Career Growth And Perceived Organizational Support On Turnover Intention: The Role Of Organizational Commitment Among Indonesian Millennial Employees - Nabila Ghina Zahirah; Aryana Satrya (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The Millennial generation, which dominates the world’s current population, can be both an opportunity and a challenge due to its characteristic of being unable to stay in a company for a long period of time like previous generations. This research aims to measure the influence of career growth and perceived organizational support on turnover intention among millennial employees, mediated by organizational commitment. Empirical data were collected from 316 respondents using an online survey assessed through a 7-point Likert scale. The respondents are millennial employees (born between 1980 and 1996) in Indonesia who are currently working in a company with a minimum tenure of 2 years. The data were analyzed using Structural Equation Modeling (SEM) with Lisrel 8.8 software. The results show that career growth and perceived organizational support can increase commitment and reduce employees' intention to leave. It was additionally discovered that organizational commitment significantly serves as a mediating factor in the relationship between career growth and perceived organizational support regarding turnover intention